2021
DOI: 10.1111/jerd.12732
|View full text |Cite
|
Sign up to set email alerts
|

Whitening effect of 35% hydrogen peroxide in simulation of tooth with orthodontic bracket

Abstract: Objective To evaluate the color change and tooth whitening perception in 2 and 3 mm dental specimens simulating the orthodontic bracket for a 14‐day period. Materials and methods Forty bovine tooth fragments (8 × 7 mm) of 2 mm (G2, n = 20) and 3 mm (G3, n = 20) were divided into Control (C: without bracket simulation and whitening) and Experimental (E: with composite resin simulating orthodontic bracket cementation area). Analyses of color change (ΔE00) and perception of tooth whitening (WID) were performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 30 publications
1
21
0
8
Order By: Relevance
“…28,29 The in-office and at-home bleaching procedures showed statistically greater color changes and similarity around the bracket area, corroborating with previous studies. 18,19,21,22,25,30 The area under the bracket showed greater color alteration and tooth whiteness, when compared with the area around the bracket, for the non-whitening toothpaste, 2% hydrogen peroxide whitening toothpaste, and at-home bleaching procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 The in-office and at-home bleaching procedures showed statistically greater color changes and similarity around the bracket area, corroborating with previous studies. 18,19,21,22,25,30 The area under the bracket showed greater color alteration and tooth whiteness, when compared with the area around the bracket, for the non-whitening toothpaste, 2% hydrogen peroxide whitening toothpaste, and at-home bleaching procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies [14][15][16][17][18][19] have evaluated the efficacy of different dental bleaching agents under orthodontic brackets, no study has evaluated the whitening toothpastes. Since many patients wearing orthodontic appliances perceive changes in the shade of their teeth, and whitening toothpaste is an easily accessible product, 12 its efficacy needed to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, a simple method was suggested for evaluating the whitening effect of hydrogen peroxide on tooth stains. 272 Dental specimens of 2 and 3 mm were prepared by using an orthodontic bracket, and the color change and perception of tooth whitening were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, clinical trials have been directly conducted to confirm the effectiveness of certain whitening agents, but these are now outlawed. In a recent study, a simple method was suggested for evaluating the whitening effect of hydrogen peroxide on tooth stains . Dental specimens of 2 and 3 mm were prepared by using an orthodontic bracket, and the color change and perception of tooth whitening were evaluated.…”
Section: Discussionmentioning
confidence: 99%